Temperature-independent accelerometer using a fiber Bragg grating incorporating a biconical taper - Ni, Kai (2013)
An intensity-modulated optical fiber accelerometer is proposed and experimentally demonstrated by using a fiber Bragg grating (FBG) incorporating a biconical fiber taper. Acceleration-induced microbending of the fiber taper region introduces various attenuation to the light, so that acceleration can be measured from changes of the optical power of the reflected light from the FBG. This power detection method reduces the cost and complexity of the sensor setup since only photodetector is required for the signal detection. In the static measurement, a relatively large range of 5g (g is gravity, equals to 9.8 m/s2) with sensitivity of 4.85 nW/g is achieved. Vibration measurements have also been carried out with a frequency up to 20 Hz. The proposed accelerometer is nearly independent of temperature because the reflected optical power of the FBG is insensitive to temperature.